2012
DOI: 10.1111/j.1442-200x.2012.03639.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of fetal echocardiography: A 17 year single‐institution experience in Japan

Abstract: Prenatal diagnosis of CHD enables planned labor, prevents ductal shock, and reduces prostaglandin E1 side-effects and medical expenditure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 15 publications
2
12
0
1
Order By: Relevance
“…If there are no collateral vessels, the ductus arteriosus acts as the only supplier of arterial blood to the abdominal organs in IAA patients. In these cases, closure of the ductus arteriosus leads to multiple organ dysfunction and shock, called ''ductal shock'' [8]. In the present case, the patient was alive for 21 days, consistent with previous papers reporting the median age at death to be 4-10 days [3,4,9], and suggesting that closure of the ductus arteriosus is often prolonged in these patients.…”
Section: Discussionsupporting
confidence: 87%
“…If there are no collateral vessels, the ductus arteriosus acts as the only supplier of arterial blood to the abdominal organs in IAA patients. In these cases, closure of the ductus arteriosus leads to multiple organ dysfunction and shock, called ''ductal shock'' [8]. In the present case, the patient was alive for 21 days, consistent with previous papers reporting the median age at death to be 4-10 days [3,4,9], and suggesting that closure of the ductus arteriosus is often prolonged in these patients.…”
Section: Discussionsupporting
confidence: 87%
“…Viewing the problem from the prenatal perspective, there are limited published data that documents the incidence of IUFD amongst a wide range of CHD. In fact, the risk for stillbirth in the fetus with CHD varies depending on the study population analyzed (see Table ) but has been noted to be as high as 25–37% …”
Section: Discussionmentioning
confidence: 99%
“…Previous publications have noted up to a 20% incidence of genetic and extra‐cardiac anomalies (ECA) in the fetus with CHD . The reported incidence of IUFD in select populations of CHD varies according to the reference sited but ranges anywhere from 1 to 38% . The risk for IUFD in the fetus with CHD has led some practitioners to advocate a scheduled delivery prior to full term to control the timing of delivery with the goal of optimizing the postnatal care of the baby.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a duplication of 22q11.2 region can also lead to 22q11.2 microduplication syndrome which has features overlapping 22q11.2 deletion syndrome [6,7]. Recent evidence have suggested that infant mortality associated with CHDs has improved considerably over recent decades [810]. Increasing sensitivity of diagnosis means that early preparation can be made for termination, surgery therapy and psychology, with the potential to improve survival [11].…”
Section: Introductionmentioning
confidence: 99%